THE EFFECT OF FISHBOWL METHOD ON STUDENTS’ SPEAKING ABILITY (A Study at the Tenth Grade of SMA Negeri 1 Sitahuis 2018/2019 Academic Year) - SARAYANTI SIMBOLON (JURNAL LINER (Language Intelligence and Educational Research), 2019)
Purpose of this research is to know the application of fishbowl method on students’ speaking ability at the tenth grade of SMA Negeri 1 Sitahuis 2018/2019 Academic Year, to know the students’ speaking ability before and after using fishbowl method at the tenth grade of SMA Negeri 1 Sitahuis 2018/2019 Academic Year, and to know whether there is any significant effect of fishbowl method on students’ speaking ability at the tenth grade of SMA Negeri 1 Sitahuis 2018/2019 Academic Year. The research method is use by experimental method. Population in this research is all of the tenth grade of SMA Negeri 1 Sitahuis are 128 students. Sample are 32 students which taken by systematic sampling. Instrument of collecting data use observation sheet and oral test. The result mean of the application of fishbowl method is 3.03, based on the technique of analysis data the criterion of score using fishbowl method with categorized “Good”, the result students’ speaking ability before using fishbowl method is 59.25 categorized “Failing”, while after using fishbowl method is 80.18, it was categorized “Good”, to know the result of the data, the research of analysis data use by formula, the result of is 14.04 meanwhile is 2.04, it means that there is a significant effect of fishbowl method on students’ speaking ability at the tenth grade of SMA Negeri 1 Sitahuis 2018/2019 Academic Year or Ha is accepted. Keywords: fishbowl method, speaking